2020
DOI: 10.1109/access.2020.2993671
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Online Impulse Buying Behavior in Social Commerce: A Systematic Literature Review

Abstract: This paper funded by Universiti Teknologi Malaysia (UTM) under the University Research grant number (Q.J130000.2528.18H56).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 101 publications
(141 reference statements)
0
40
0
10
Order By: Relevance
“…Abdelsalam et al (2020) developed a causal-chain framework for online impulse buying in social commerce based on the S–O–R model which determined the various factors (i.e. social-related factors, website-related factors, consumer characteristics, and marketing-associated factors) which influenced the consumer's online impulse buying behaviors and their interrelationships in an S-commerce context.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdelsalam et al (2020) developed a causal-chain framework for online impulse buying in social commerce based on the S–O–R model which determined the various factors (i.e. social-related factors, website-related factors, consumer characteristics, and marketing-associated factors) which influenced the consumer's online impulse buying behaviors and their interrelationships in an S-commerce context.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As consumer expectations keep rising and e-commerce sales continue to surge, the popularity of online shopping and the widespread adoption of social networking sites (SNSs) have recently led to a new e-commerce paradigm called social commerce (s-commerce). S-commerce, considered a subset of e-commerce, uses social media to facilitate social interactions between consumers and brands, promoting the buying and selling of products and services (Abdelsalam et al , 2020; Hossain and Kim, 2020). Those trends pose a great challenge for traditional stores to keep up.…”
Section: Introductionmentioning
confidence: 99%
“…Researcher have shared that the business activities and consumer buying patterns are changed due to Covid-19 ( Ting et al, 2020 ; Cogley, 2020 ; Mao, 2020 ). Consumer buying behaviour is complicated and subjective reality especially in the presence of social commerce ( Aragoncillo and Orus, 2018 ; Abdelsalam et al, 2020 ; Algharabat et al, 2020 ). Other researchers stated social media enhanced the information sharing among consumers through online rating, sponsored ads, online reviews, social motivation, and social influencers ( Alalwan et al, 2017 ; Alalwan, 2018 , 2020 ).The social media has increased the online purchasing behaviour therefore many businesses and consumers are engaged because it facilitates to take optimal buying decision ( Alalwan, 2018 ; Alalwan et al, 2019 ; Baker Qureshi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Now with COVID-19 global pandemic, online shopping has been increasing at a rapid pace and more studies are needed to capture the consumer behavior during and postglobal pandemic. Some of the latest studies found that online shopping (e-shopping) has also resulted in increase in impulse buying (Abdelsalam et al, 2020;Verma and Singh, 2019). As user behavior is undergoing significant changes in the present day post-COVID global pandemic, more and more studies are needed to unravel these changes.…”
Section: Discussionmentioning
confidence: 99%